Trends in Obesity and Metabolic Status in Northern and Southern China Between 2012 and 2020 - Li, Ying; Yang, Lin; Yin, Lu; Liu, Qingqi; Wang, Yaqin; Yang, Pingting; Wang, Jiangang; Chen, Zhiheng; Li, Xiaohui; Yang, Qinyu; He, Yongmei; Huang, Xin (Frontiers in Nutrition, 2022)
Background: The trends of obesity-associated metabolic status in Chinese are lacking, especially those from different regions. Objectives: To examine the trends of obesity and metabolic status among Chinese population in 2012-2020. Methods: In a series cross-sectional study, data on 256,782 participants surveyed between 2014 and 2020 in Beijing, northern China, and 697,170 participants surveyed between 2012 and 2020 in Hunan, southern China were analyzed. Anthropometrics, blood pressure measurements, and blood tests were performed according to standard protocols. Trends in obesity and metabolic status were evaluated using the Joinpoint software. Results: Based on age- and sex-standardized values, the mean BMI values in northern and southern participants were 23.94 (95%CI: 23.93, 23.95) and 23.68 (95%CI: 23.67, 23.69) kg/m2, respectively. Between 2014-2020, the overall obesity prevalence among northern participants increased from 12.70% (95%CI: 12.17%, 13.23%) to 14.33% (95% CI: 13.97%, 14.70%) (P=0.009), mainly derived by the 20-39 and 40-59 age groups. Moreover, the prevalence of metabolically healthy obese significantly increased from 2.07% (95%CI: 1.84%, 2.30%) to 4.33% (95% CI: 4.13%, 4.53%) in Northerners. Between 2012-2020, no significant trend in obesity was found among overall southern participants, but the prevalence of metabolically unhealthy obese significantly increased from 5.36% (95% CI: 5.18%, 5.54%) to 7.35% (95% CI: 7.11%, 7.58%), mainly derived by the 20-39 and 40-59 age groups. Conclusions: The trends in obesity and metabolic status were different between southern and northern Chinese. A national weight control plan is needed in China, focusing on young and middle-aged population.